Communications Between Changes Of Monthly Average Values Of The General Content Of Ozone Over The Arctic With Temperature Of Waters, Pereno-Simykh The Currents, Forming Gulf Stream, At The Modern Drowning Of Climate - Холопцев, О. В.; Кузьменко, В. Г. (Харківський національний університет імені В.Н.Каразіна, 2014)
Statistical communications of interannual changes of Total ozon distributions on the Arctic in February – May are revealed, and changing and also advancing them on time of changes of average superficial temperatures of the Caribbean Sea and the water area of Atlantic in a zone of its North current Passatnogo which from 1979 for 2010 noticeably amplified and nowadays at the revealed values of temporary shifts between them are significant. Stability of their strengthening allows to assume that at a further drowning of climate they will amplify even more that testifies to expediency of their account when modeling and forecasting. Выявлены статистические связи межгодовых изменений общего содержания озона над Арктикой в феврале – мае, а также опережающих их по времени изменений средних поверхностных температур Карибского моря и акватории Атлантики в зоне ее Северо-Пассатного течения, которые за период с 1979 г. по 2010 г. ощутимо усилились и ныне являются значимыми. Устойчивость их усиления позволяет предполагать, что при дальнейшем потеплениии климата они усилятся еще больше, что свидетельствует о целесообразности их учета при моделировании и прогнозировании. Визначено статистичні зв'язки міжрічних змін загального вмісту озону понад Арктикою у лютому-травні, а також змін середніх поверхневих температур Карибського моря та акваторії Атлантики в зоні її Північно-пасатної течії, котрі за період з 1979 р. по 2010 р. відчутно посилилися, та у сьогоденні є суттєвими. Стійкість їх посилення дозволяє припускати, що при подальшому потеплінні клімату вони посиляться ще більше. Це свідчить про доцільність їх урахування при моделюванні та прогнозуванні.